ANALISIS SEKTOR LOGISTIK DALAM RANGKA KELANCARAN ARUS BARANG DAN PENINGKATKAN DAYA SAING KOMODITI EKSPOR DAERAH (LOGISTICS SECTOR ANALYSIS IN ORDER TO BRING SMOOTHNESS THE FLOW OF GOODS AND TO IMPROVE THE COMPETITIVENESS OF LOCAL EXPORT COMMODITIES) - Haryotejo, Bagas (Jurnal Borneo Administrator, 2013)
A country with an efficient logistics services sector will be more competitive than those with less efficient systems. Indonesia logistical conditions reflects the fact that the total cost prior to shipment and inland transportation in the country reached more than 40% of the total cost of logistics. It's certainly encouraging high-cost economy and also reduces the competitiveness of Indonesian products. This emphasizes that the logistics become the most important sectors in enhancing the competitiveness of a country's export products. The applied analysis method in this research is Analytical Hierarchy Process (AHP) based on two hierarchies, namely: (1) hierarchy that includes the domestic distribution of current (effective), efficient distribution of domestic and Supply Chain, and (2) hierarchy which includes six indicators, namely the harmonization of central/ regional, infrastructure improvement, human resource development, the elimination of unofficial fees, law enforcement for those who break the rules, and do not do anything (do nothing). Based on the synthesis of the six policy choices, infrastructure improvements, removal of unofficial fees and Harmonization of both national and local regulations were the policy priorities that must be taken by the Government to realize the smooth flow of goods in order to create competitiveness of Indonesian export products.Keywords: Logistics, AHP, CompetitivenessNegara dengan sektor jasa logistik yang efisien akan lebih kompetitif dibandingkan negara dengan jasa logistik yang kurang efisien. Kondisi logistik Indonesia mencerminkan bahwa total biaya sebelum pengiriman dan transportasi darat mencapai lebih dari 40% dari total biaya logistik. Ini tentu mendorong ekonomi biaya tinggi dan mengurangi daya saing produk Indonesia. Hal ini membuat logistik menjadi sektor yang paling penting dalam meningkatkan daya saing produk ekspor. Metode analisis yang digunakan dalam penelitian ini adalah Analytical Hierarchy Process (AHP) didasarkan pada dua hierarki, yaitu: (1) hierarki yang meliputi distribusi domestik arus distribusi (efektif), efisien Rantai Pasokan domestik dan, dan (2) hierarki yang meliputi enam indikator, yaitu harmonisasi pusat / daerah, perbaikan infrastruktur, pengembangan sumber daya manusia, penghapusan biaya tidak resmi, penegakan hukum bagi mereka yang melanggar aturan, tidak melakukan apa-apa (do nothing). Berdasarkan sintesis dari enam pilihan kebijakan, perbaikan infrastruktur, penghapusan biaya tidak resmi dan Harmonisasi peraturan baik nasional dan lokal adalah prioritas kebijakan yang harus dilakukan oleh Pemerintah untuk mewujudkan kelancaran arus barang dalam rangka menciptakan daya saing produk ekspor.Kata Kunci : Logistik, AHP, Daya saing